Analyzing Coaches' Skills: A Survey of Table Tennis Coaches in Riau Province and DIY Province, Indonesia - Ali Mandan; Syahriadi; Trisnar Adi Prabowo (Indonesian Journal of Physical Education and Sport Science)
Studi purpose. The purpose of this study was to determine the ideal coach skills for Table Tennis.